Comparison of epidural dexmedetomidine to fentanyl in reducing ropivacaine dose in Programmed Intermittent Epidural Bolus plus Patient Controlled Epidural Analgesia during labor: A randomized, double-blind, controlled study - Pang, Ru-Ying; Shen, Yao-Hua; Jin, Xiao-Qin; Xu, Hai-Feng; Wang, Yang; Zhu, Bin-Xiang; Lin, Su-Feng; Xiao, Fei (Frontiers in Medicine, 2022)
Background Dexmedetomidine has been documented to reduce the dose of both intrathecal local anesthetic during cesarean delivery, and the concentration of ropivacaine needed for inducing analgesia during labor. However, few studies have compared adjuvant dexmedetomidine to fentanyl on how they impact the dose of ropivacaine required during labor. The aim of the current study was to evaluate the efficacy of epidural dexmedetomidine at doses of 0.3, 0.4, or 0.5 μg/ml and 2 μg/ml of fentanyl (the traditional clinical concentration), when added to epidural 0.125% ropivacaine. Methods This was a randomized, double-blinded study that comprised one hundred eighty-eight patients, allocated into four groups receiving either epidural fentanyl at 2μg/ml, or dexmedetomidine at 0.3, 0.4, or 0.5μg/ml for labor analgesia. The primary outcome was the amount of ropivacaine necessary per hour. Secondary outcomes included visual analogue pain scale (VAS), motor block (Bromage Scale), side effects, patient satisfaction, and neonatal outcomes. Results At the completion of the study, data from 165 participants were analyzed. The mean hourly amount of epidural ropivacaine administered was 16.2 ± 3.3, 14.0 ± 3.1, 13.1 ± 3.7 and 12.1 ± 2.5 ml/h in the 2 μg/ml fentanyl group, and the 0.3, 0.4 and 0.5 μg/ml dexmedetomidine groups, respectively. There was a significant difference among groups in the mean hourly consumption of epidural ropivacaine (P< 0.0001 for 1 way ANOVA). The time of PCEA (patient-controlled epidural analgesia) was significantly higher in the fentanyl group than in the three dexmedetomidine groups (P< 0.001), and similar among the dexmedetomidine groups. The mean values of the VAS among all groups were similar over time, P > 0.05. The incidence of pruritus in the fentanyl group was 17.5%, whereas no patient experienced pruritus in any of the dexmedetomidine groups, P < 0.0001. Conclusion The study demonstrated that epidural dexmedetomidine (0.3 and 0.4μg/ml) was superior to standard dose epidural fentanyl in reducing the mean hourly amount of ropivacaine administered, and minimizing opioid-related side effects. Further large and multi-center studies would be necessary to confirm the benefits of dexmedetomidine, and potentially serve as an alternative to opioids for routine use in labor analgesia.